Elemental distributions in the uppermost Permian Changxing Fm. in the Meishan C section - Saito, Ryosuke; Wörmer, Lars; Taubner, Heidi; Kaiho, Kunio; Takahashi, Satoshi; Tian, Li; Ikeda, Masayuki; Summons, Roger E; Hinrichs, Kai-Uwe (In: Saito, R et al. (2022): An expanded record of proxy data in the uppermost Permian Changxing Fm. in the Meishan C section [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.952297, 2022)
An M4 Tornado Micro-XRF spectrometer system (Bruker Nano Analytics) equipped with micro-focused Rh source (50 kV, 600 µA) and poly-capillary optics (25-µm spot size) was used for elemental mapping. Measurements were conducted under vacuum (20 mb) conditions with a resolution of 50 µm per pixel and a scan time of 60 ms per pixel. Maps of Al, Fe and S (counts) were exported from M4 Tornado Software version 1.3 as xy-matrices to csv files and further processed.
Keywords: end-Permian mass extinction; Meishan; micro-XRF